Modified ceramic coating and preparation method thereof

The reaction products of modified polyether ether ketone, polysiloxane and silica sol in modified ceramic coatings form a dense bottom oil layer, which solves the problem of residual odor after use of ceramic coatings, and achieves better user experience and heat resistance.

CN120041086APending Publication Date: 2025-05-27WUHAN SUPOR COOKWARE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510228012.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

Existing ceramic coatings tend to retain odors such as coffee after use, affecting consumers' usage experience.

Method used

Modified ceramic coatings are used, which are liquid coatings dispersed in solvents with reaction products of modified polyether ether ketone, polysiloxane and silica sol as base oil coatings to form a dense base oil layer to reduce binding with odor molecules.

Benefits of technology

It effectively avoids odor residues, improves consumer experience, and improves the density and heat resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005292285240000261
    Figure BDA0005292285240000261
Patent Text Reader

Abstract

The invention provides a modified ceramic coating and a preparation method thereof. Wherein the modified ceramic coating takes a liquid coating as a base oil coating, the liquid coating is formed by dispersing a reaction product of modified polyether-ether-ketone, polysiloxane and silica sol in a solvent, and the modified polyether-ether-ketone is at least one of hydroxylated polyether-ether-ketone and a derivative of the hydroxylated polyether-ether-ketone. According to the modified ceramic coating provided by the embodiment of the invention, the base oil layer formed by the base oil coating is high in density and is not easy to crack and combine with odor molecules in the use process, so that peculiar smell residues can be avoided to a great extent, and the use experience of consumers can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings, and in particular to a modified ceramic coating and a preparation method thereof. Background Art

[0002] When a container (e.g., a ceramic-coated water cup) with a ceramic coating on the inner wall is soaked in some odorous beverages (e.g., coffee), even if the inside is cleaned after use, a relatively obvious coffee smell will remain, and the residual smell usually takes a long time (usually more than half a month) to gradually dissipate. These residual smells are obvious and "linger for a long time", which seriously affects the consumer's experience. Summary of the invention

[0003] The present application aims to at least solve the problem in the above-mentioned prior art or related art that the residual smell of the container after use is obvious and "lingering", which seriously affects the consumer's experience of use.

[0004] To achieve the above-mentioned objectives, a first aspect embodiment of the present application provides a modified ceramic coating, wherein the modified ceramic coating uses a liquid coating formed by dispersing the reaction product of modified polyetheretherketone, polysiloxane and silica sol in a solvent as a primer coating, wherein the modified polyetheretherketone is at least one of a hydroxylated polyetheretherketone and a derivative of a hydroxylated polyetheretherketone.

[0005] According to the modified ceramic coating provided in the embodiment of the present application, the base oil layer formed by the base oil coating has a high density, is not prone to cracks during use, and is not easy to combine with odor molecules. Therefore, it can avoid odor residue to a large extent, thereby improving the consumer's usage experience.

[0006] In some embodiments, based on the total weight of the base oil coating being 100%, the weight of the reaction product accounts for 40% to 55% of the total weight of the base oil coating, and the remainder is the solvent. In this way, a dense base oil layer is formed by the base oil coating, so that the container having the base oil layer is not easily combined with odor molecules during use.

[0007] In some embodiments, the base oil coating further comprises pigments and fillers dispersed in the liquid coating, and based on the total weight of the base oil coating being 100%, the weight of the reaction product accounts for 40% to 55% of the total weight of the base oil coating, the weight of the pigments and fillers accounts for 20% to 30% of the total weight of the base oil coating, and the remainder is solvent. In this way, not only can a dense base oil layer be formed by the base oil coating, so that the container having the base oil layer is not easily combined with odor molecules during use, but the formed base oil layer can also have a certain color and / or wear resistance.

[0008] In some embodiments, the reaction product has a network structure, which can further improve the density of the bottom oil layer.

[0009] In some embodiments, the polysiloxane includes at least one of polymethylsiloxane, polymethylphenylsiloxane and polyethylsiloxane, and these polysiloxanes can exhibit relatively better non-stickiness.

[0010] In some embodiments, the modified ceramic coating further comprises a topcoat coating, and the topcoat coating and the basecoat coating are placed separately, wherein the topcoat coating comprises a dispersion solvent and a siloxane polymer dispersed in the dispersion solvent; wherein the siloxane polymer comprises a conversion product of polysiloxane and silica sol, or comprises a polymer of dimethylsiloxane and silicon dioxide, and a conversion product of polysiloxane and silica sol.

[0011] In the above embodiments, the conversion product of polysiloxane and silica sol, the polymer of dimethylsiloxane and silicon dioxide, and the conversion product of polysiloxane and silica sol can ensure the non-stick performance as the top oil layer. In addition, compared with other existing top oil coatings, the modified top oil coating does not contain fillers, pigments and other substances (forming a transparent coating after sintering), and is only a silane material (the conversion product of polysiloxane and silica sol, the polymer of dimethylsiloxane and silicon dioxide, and the conversion product of polysiloxane and silica sol), so it can have improved non-stick properties. In addition, since the modified topcoat paint does not contain fillers, pigments, etc. (these pigments and fillers are powdered inorganic substances and will not participate in the reaction during the formation and maturation process), the formed topcoat layer naturally does not contain powdered inorganic substances such as pigments and fillers embedded in the coating. Therefore, it can have an improved surface density due to the lack of doped particles, and reduce the inducement for the formation of gaps in itself (doped with powdered inorganic substances such as pigments and fillers). Even in the later use process, gaps are not likely to appear or the gaps are not likely to expand further. There will be no part where powdered inorganic substances such as pigments and fillers come into contact with odor molecules and are adsorbed, thereby further reducing the coffee-like odor substances adsorbed in the initial use of the container, avoiding odor residue, and ensuring the durability of the anti-odor performance, thereby enhancing the consumer's experience.

[0012] In some embodiments, when the siloxane polymer includes a conversion product of polysiloxane and silica sol, based on the total weight of the topcoat coating being 100%, the weight of the conversion product of polysiloxane and silica sol accounts for 60%-80% of the total weight of the topcoat coating, and the balance is a dispersing solvent; or, when the siloxane polymer includes a conversion product of a polymer of dimethylsiloxane and silica, polysiloxane and silica sol, based on the total weight of the topcoat coating being 100%, the weight of the conversion product of dimethylsiloxane and silica, polysiloxane and silica sol accounts for 60%-80% of the total weight of the topcoat coating, and the balance is a dispersing solvent.

[0013] In these embodiments, the conversion product has a suitable weight ratio, and can form a coating in which the conversion product is uniformly dispersed in a dispersion solvent, so as to ensure that the surface oil layer formed thereby is uniform and dense.

[0014] According to a second aspect of the present application, a method for preparing a modified ceramic coating is provided, wherein the method for preparing the modified ceramic coating comprises the following steps: forming a mixed slurry comprising modified polyetheretherketone, polysiloxane and silica sol, wherein the modified polyetheretherketone is at least one of hydroxylated polyetheretherketone and a derivative of hydroxylated polyetheretherketone; ripening the mixed slurry to obtain a liquid coating formed by dispersing a reaction product comprising the modified polyetheretherketone, polysiloxane and silica sol in a solvent as a primer coating, thereby preparing the modified ceramic coating.

[0015] According to the preparation method of the modified ceramic coating provided in the embodiment of the present application, in the base oil coating, the modified polyetheretherketone will be formed in the pores of the polymethylsiloxane-silica sol network structure during the sol-gel reaction between polymethylsiloxane and silica sol, and react with polymethylsiloxane, so that the main film-forming substance in the base oil coating (the reaction product of modified polyetheretherketone, polysiloxane and silica sol) is more compact as a whole, thereby improving the density of the formed base oil layer, and the container with the base oil layer is not easy to crack during use, especially not easy to crack the surface oil layer on it due to cracks in itself, so it is not easy to combine with odor molecules, so it can avoid odor residue to a large extent, and improve the consumer's use experience. In addition, the main film-forming substance itself has better heat resistance, so the heat resistance of the base oil layer formed by it can also be improved, so when brewing odorous liquids (for example, brewing coffee), it is not easy to make the base oil layer "heat expand", thereby reducing the possibility of cracks in the base oil layer due to "heat expansion".

[0016] In some embodiments, in the mixed slurry, the weight ratio of the modified polyetheretherketone, the polysiloxane and the silica sol is (0.1-0.5):(30-40):(10-15). Specifically, in the mixed slurry, the weight of the modified polyetheretherketone is 0.2 parts to 1.0 parts, the weight of the polysiloxane is 30 parts to 40 parts, the weight of the silica sol is 10 parts to 15 parts, and the weight of the solvent is 10 parts to 30 parts.

[0017] In these embodiments, the modified polyetheretherketone, polysiloxane and silica sol in the mixed slurry have a suitable weight ratio, which can be beneficial to the formation of the main film-forming substance (the reaction product of modified polyetheretherketone, polysiloxane and silica sol) after ripening and in the process of forming the modified ceramic coating, thereby improving the anti-odor performance while ensuring the non-stickiness of the modified ceramic coating.

[0018] In some embodiments, the forming of a mixed slurry comprising modified polyetheretherketone, polysiloxane and silica sol comprises mixing the modified polyetheretherketone and silica sol, adjusting the pH value to 3-6, and then adding the polysiloxane to form a mixed slurry comprising polyetheretherketone, polysiloxane and silica sol, in preparation for the maturation of the mixed slurry.

[0019] In some embodiments, the step of maturing the mixed slurry includes: stirring the mixed slurry at a temperature of 15°C-25°C for 4h-10h and maintaining the pH value at 3-6 to mature the mixed slurry, which is more conducive to the formation of the reaction product of modified polyetheretherketone, polysiloxane and silica sol.

[0020] In some embodiments, the mixed slurry further comprises pigments and fillers and solvents, wherein, in the mixed slurry, the weight portion of the modified polyetheretherketone is 0.1-0.5 parts, the weight portion of the polysiloxane is 30-40 parts, the weight portion of the silica sol is 10-15 parts, the weight portion of the pigments and fillers is 20-30 parts, and the weight portion of the solvent is 10-30 parts. Including a certain amount of pigments and fillers in the mixed slurry for forming the primer coating can improve the strength and color of the primer layer formed by the primer coating without affecting the density of the primer layer formed by the primer coating as much as possible.

[0021] According to the third aspect of the present application, a modified ceramic coating is provided, wherein the modified ceramic coating comprises a primer layer, the primer layer comprises a cross-linked product layer of a reaction product of modified polyetheretherketone, polysiloxane and silica sol, wherein the modified polyetheretherketone is at least one of a hydroxylated polyetheretherketone and a derivative of a hydroxylated polyetheretherketone.

[0022] According to the modified ceramic coating provided in the embodiment of the present application, a cross-linked product layer of the reaction product of modified polyetheretherketone, polysiloxane and silica sol is used as the base oil layer. The coating is dense and not prone to cracks during use, and is not easy to combine with odor molecules. Therefore, it can avoid odor residue to a large extent and enhance the consumer's experience.

[0023] In some embodiments, a pigment filler is also dispersed in the crosslinked product layer of the reaction product of the modified polyetheretherketone, polysiloxane and silica sol. In this way, the strength of the base oil layer can be balanced while ensuring the density of the base oil layer, thereby inhibiting base oil cracks to further avoid residual taste and improve the consumer's experience.

[0024] In some embodiments, based on the total weight of the base oil layer as 100%, the weight of the cross-linked product layer of the reaction product of the modified polyetheretherketone, polysiloxane and silica sol accounts for 60% to 70% of the total weight of the base oil layer, and the weight of the color filler accounts for 30% to 40% of the total weight of the base oil layer. In this way, the strength of the base oil layer can be optimized while ensuring the density of the base oil layer, thereby inhibiting base oil cracks to further avoid flavor residue and enhance the consumer experience.

[0025] In some embodiments, the color filler includes a pigment and a filler, the pigment includes at least one of titanium dioxide, carbon black, copper chrome black, iron oxide, pigment brown and pigment orange, and the filler includes at least one of bentonite, kaolin, mica powder, montmorillonite, silicon carbide, aluminum oxide and silicon dioxide. In this way, the strength of the base oil layer can be further optimized while ensuring the compactness of the base oil layer, thereby inhibiting base oil cracks to further avoid taste residue, and ensuring the color of the base oil layer to enhance the consumer's experience.

[0026] In some embodiments, the weight ratio of the pigment to the filler is 1:2-2:1. The pigment and the filler have a suitable weight ratio, which can take into account both strength improvement and color improvement to a certain extent without excessively affecting the density of the base oil layer.

[0027] In some embodiments, the modified ceramic coating further comprises a top oil layer formed on the base oil layer; wherein the top oil layer is a cross-linked product layer of a conversion product of polysiloxane and silica sol, or the top oil layer is a cross-linked product layer of a conversion product of a polymer of dimethylsiloxane and silicon dioxide, polysiloxane and silica sol.

[0028] In these embodiments, the modified ceramic coating has a double-layer structure, which can further enhance the advantages of the primer-modified polyetheretherketone. When there is no modified polyetheretherketone in the primer, thermal expansion will cause gaps in the primer, and cracks may also appear in the thinner top oil, which cannot block the gaps. When the primer contains modified polyetheretherketone, high-temperature thermal expansion has no obvious effect on the cracks in the coating, and the small gaps in the primer can be further sealed after the top oil is applied.

[0029] According to a fourth aspect of the present application, a container is provided, wherein the container comprises a container body and a modified ceramic coating formed on the inner wall surface of the container body, wherein the modified ceramic coating is the modified ceramic coating described above; or, the modified ceramic coating is a layer formed by a modified ceramic coating, wherein the modified ceramic coating is the modified ceramic coating described above or is a ceramic coating prepared according to the method for preparing a modified ceramic coating described above.

[0030] In some embodiments, the container is an inner liner of a cup, a pot or a kettle, and is applicable to a variety of product types, and can provide a variety of product types. DETAILED DESCRIPTION

[0031] The following specific embodiments are provided to help the reader obtain a comprehensive understanding of the methods, devices and / or systems described herein. However, after understanding the disclosure of the present application, various changes, modifications and equivalents of the methods, devices and / or systems described herein will be clear. For example, the order of operations described herein is only an example and is not limited to those orders set forth herein, but can be changed as will be clear after understanding the disclosure of the present application, except for operations that must occur in a specific order. In addition, for greater clarity and simplicity, the description of features known in the art may be omitted.

[0032] The ceramic coating includes a single-system or a dual-system ceramic coating. The single-system ceramic coating includes only a topcoat coating, while the dual-system ceramic coating includes a basecoat coating and a topcoat coating that are independently placed and used separately.

[0033] The existing ceramic coating is a liquid coating with the reaction product (silicone polymer) formed by polysiloxane and silica sol as the main non-stick component. When the container (for example, a ceramic coated water cup) is sintered after spraying the ceramic coating on the inner wall, it will still have a relatively obvious coffee smell even if the inside of the container is cleaned after use. The residual smell usually takes a long time (usually more than half a month) to gradually dissipate. These residual smells are obvious and "linger for a long time", which seriously affects the consumer's experience.

[0034] After the existing ceramic coating is air-sprayed and sintered, the coating formed is easy to physically absorb odor molecules, so that the residual smell of the container (cup) is obvious and "long-lasting". After research, the inventor found that this is mainly because the coating has large pores and cracks are easy to appear when used at high temperatures, which makes it easy for odor molecules to be absorbed in the corresponding pores and cracks.

[0035] Specifically, the coating includes a base oil layer and a surface oil layer formed on the base oil layer. When the base oil layer has cracks, although the surface oil layer has the function of covering the "crack" defects of the base oil layer, since the surface oil layer is usually thin, generally only 3 microns to 6 microns, the thinner surface oil layer still cannot last long and effectively inhibit the continued extension of the "crack" defects of the base oil layer, thereby easily causing cracks to appear in the surface oil layer.

[0036] In the present application, a liquid coating formed by mixing and ripening modified polyetheretherketone, polysiloxane and silica sol and dispersing the reaction product of modified polyetheretherketone, polysiloxane and silica sol in a solvent is formed as a primer coating, and the reaction product is used as the main film-forming substance in the primer coating. When the primer coating is sprayed on the container body to form a primer layer, the main film-forming substance (sol-gel) in the primer coating will cross-link with each other under the action of the temperature in the sintering stage, thereby forming a dense primer layer as a modified ceramic coating according to the present application.

[0037] According to the first aspect of the present application, a modified ceramic coating is provided, at least for cups, wherein the modified ceramic coating uses a liquid coating comprising a reaction product of modified polyetheretherketone, polysiloxane and silica sol dispersed in a solvent as a primer coating, and the reaction product serves as the main film-forming substance of the primer coating, wherein the modified polyetheretherketone is at least one of a hydroxylated polyetheretherketone and a derivative of a hydroxylated polyetheretherketone.

[0038] In the present application, the main film-forming substance refers to a substance in the base oil coating that can independently form a continuous dry film with a certain strength, that is, a substance that is retained in the base oil layer to provide certain properties (for example, non-stickiness, density).

[0039] According to the modified ceramic coating provided in the embodiment of the present application, the base oil layer formed by the base oil coating has a high density, is not prone to cracks during use, and is not easy to combine with odor molecules. Therefore, it can avoid odor residue to a large extent, thereby improving the consumer's usage experience.

[0040] According to the present application, the modified polyetheretherketone is specifically a reduction-modified polyetheretherketone or a derivative of the reduction-modified polyetheretherketone. According to some embodiments, the modified polyetheretherketone is specifically at least one of a hydroxylated polyetheretherketone (polyetheretherketone containing a hydroxyl group) and a derivative of a hydroxylated polyetheretherketone. Here, the hydroxylated polyetheretherketone is a compound in which at least part of the carbonyl groups on the surface of the polyetheretherketone are replaced by hydroxyl groups, and the derivative of the hydroxylated polyetheretherketone is a compound in which the carbonyl groups on the surface of the derivative of the polyetheretherketone are replaced by hydroxyl groups.

[0041] In some embodiments, the hydroxylated polyetheretherketone is obtained by converting the carbonyl groups on the surface of PEEK into hydroxyl groups through a chemical reaction.

[0042] In some embodiments, the derivative of hydroxylated polyetheretherketone may include a hydroxylated polyetheretherketone / hydroxyapatite (HA) composite material, or the derivative of hydroxylated polyetheretherketone is obtained by copolymerizing a monomer containing a hydroxyl group with a PEEK monomer to obtain a derivative of hydroxylated polyetheretherketone.

[0043] According to the present application, polysiloxane can react with silica sol and modified polyetheretherketone to form siloxane polymer as the main film-forming substance in the primer coating. According to some exemplary embodiments of the present application, polysiloxane can include at least one of polymethylsiloxane, polymethylphenylsiloxane and polyethylsiloxane.

[0044] According to the present application, polysiloxane can be obtained commercially or prepared by certain monomers. Taking polymethylsiloxane as an example, its core constituent unit is formed by polymerization of methylsilane substances, and the methylsilane substances can include at least one of methyltrimethoxysilane, methyltriethoxysilane and dimethyldimethoxysilane, but are not limited to this. In addition, in addition to including methylsilane substances, ethyl orthosilicate that forms polysiloxane by polycondensation can also be included. Here, ethyl orthosilicate plays a role in promoting the growth and crosslinking of polysiloxane chains in the reaction, thereby contributing to the formation of a more complex and stable polymer structure. Specifically, the process of synthesizing polymethylsiloxane includes a hydrolysis stage and a polycondensation stage. In the hydrolysis stage, methylsilane substances and ethyl orthosilicate undergo a hydrolysis reaction in the presence of water to generate corresponding silanol intermediates. Subsequently, in the polycondensation stage, these silanol intermediates are interconnected by a dehydration condensation reaction to form a polysiloxane chain. In terms of weight percentage, the weight of methylsilane is 85-95 parts, the weight of ethyl orthosilicate is 5-15 parts, and an appropriate amount of water is added.

[0045] According to the present application, silica sol can be obtained commercially. According to some embodiments, materials with CAS numbers of 7631-86-9 (silicon dioxide), 112945-52-5 (fumed silica), and 14808-60-7 (silicon sol) can be used as silica sol.

[0046] According to the modified ceramic coating of the present application, after the base oil coating is matured, it has a certain amount of the reaction product of modified polyetheretherketone, polysiloxane and silica sol as the main film-forming substance, thereby improving the anti-odor performance while ensuring the non-stickiness of the modified ceramic coating. Here, the reaction product of modified polyetheretherketone, polysiloxane and silica sol is specifically the product of polyetheretherketone, polymethylsiloxane and silica sol combined with each other through chemical reaction. When the base oil coating is sprayed to form a base oil layer, as the solvent and the like volatilize, the reaction product of modified polyetheretherketone, polysiloxane and silica sol can further cross-link and form a large amount of cross-linked products including polyetheretherketone, polymethylsiloxane and silica sol as the coating of the container. The coating is dense and not easy to crack, so it can ensure that the container is not easy to retain odor during use, further improving the consumer's experience.

[0047] According to some embodiments of the present application, the primer coating is mainly composed of a film-forming substance and a solvent. Taking the total weight of the primer coating as 100%, the reaction product accounts for 40% to 55% of the total weight of the primer coating, and the remainder is the solvent. In this way, a dense primer layer is formed by the primer coating, which can make the container with the primer layer not easy to combine with odor molecules during use. According to other embodiments of the present application, the primer coating is mainly composed of a film-forming substance, a pigment and a solvent. Taking the total weight of the primer coating as 100%, the weight of the reaction product accounts for 40% to 55% of the total weight of the primer coating, the weight of the pigment and the filler accounts for 20% to 30% of the total weight of the primer coating, and the remainder is the solvent. In this way, not only can a dense primer layer be formed by the primer coating, so that the container with the primer layer is not easy to combine with odor molecules during use, but also the formed primer layer can have a certain color and / or wear resistance. It should be noted that the color filler here can be a pigment and / or a filler. As an example, the pigment can be at least one of titanium dioxide, carbon black, copper chrome black, iron oxide, pigment brown and pigment orange, and the filler can be selected from at least one of bentonite, kaolin, mica powder, montmorillonite, silicon carbide, aluminum oxide and silicon dioxide.

[0048] According to the present application, the modified ceramic coating can also be a dual-system coating, that is, the ceramic coating includes a primer coating and a topcoat coating that are used independently and placed separately. Here, the primer coating is the primer coating provided in the above embodiment, and the topcoat coating can adopt the existing topcoat coating. The dual-system coating will first form a primer layer through the primer coating, and such a primer layer can provide a "solid" and dense foundation for the topcoat layer. Then, a topcoat layer is formed on the primer layer through the topcoat coating, and the topcoat layer can further seal the cracks in the primer layer caused by high temperature during use, that is, further reduce the possibility of gaps on the exposed surface of the ceramic coating that can combine with odor molecules.

[0049] According to the present application, the primer and topcoat are coatings formed by mixing the required components when they are needed. Specifically, before aging, the components can be stored separately. For example, the three substances of polyetheretherketone, polymethylsiloxane and silica sol can be diluted in the corresponding solvents and stored separately to be used as the raw material part of the primer coating for forming the modified ceramic coating. As an example, the solvent can be isopropanol, purified water, ethanol, etc., which can be more convenient to form a mixed slurry with uniform mixing. When aging is required, the diluted substances are mixed to form a modified ceramic coating. In this way, the uniformity and stability of the coating can be ensured, and the risk of unevenness, instability and other problems in the coating can be reduced. It should be noted that according to the present application, after aging, the primer and topcoat can react chemically to the maximum extent within a certain period of time to exert performance and advantages, thereby ensuring the quality and stability of the coating. As an example, the storage time of the primer and topcoat after aging does not exceed 72h.

[0050] In some preferred embodiments, the topcoat coating comprises a dispersion solvent and a siloxane polymer dispersed in the dispersion solvent, wherein the siloxane polymer may comprise a conversion product of polysiloxane and silica sol, or the siloxane polymer may further comprise a polymer of dimethylsiloxane and silicon dioxide, a conversion product of polysiloxane and silica sol.

[0051] In the case where the siloxane polymer includes a conversion product of polysiloxane and silica sol, based on the total weight of the topcoat paint being 100%, the weight of the conversion product of polysiloxane and silica sol accounts for 60% to 80% of the total weight of the topcoat paint, and the remainder is the dispersion solvent. That is, the topcoat paint may be a paint in which the reaction product of polysiloxane and silica sol is dispersed in the dispersion solvent.

[0052] As is known to all, the carbonyl and amino groups in the odorous substances in coffee substances (e.g., ketones, esters, aldehydes, pyridine-type nitrogen-containing compounds) are good hydrogen bond acceptors. When the coating formed by the ceramic coating has a large number of hydroxyl groups, it can act as a hydrogen bond donor and come into contact with beverages with a large number of hydrogen bond donors and easily adsorb the odorous substances in these beverages (e.g., odorous substances in coffee substances). That is, beverages containing hydrogen bond acceptors (e.g., certain ingredients in coffee) form hydrogen bonds with the coating surface, resulting in the ceramic coated water cup easily retaining the coffee smell even after cleaning.

[0053] The inventors have discovered that the modified ceramic coating of the present application can be obtained by blocking the formation of hydrogen bond donor groups (hydroxyl groups) during the formation of the ceramic coating, so that the number of hydrogen bond donors in the formed coating is reduced as much as possible, thereby ensuring that the cups are not easily adsorbed by coffee-like odor substances due to hydrogen bonding during use, avoiding odor residue, and improving the consumer's experience.

[0054] As some other examples, the modified topcoat coating includes a dispersing solvent and a conversion product of a polymer of dimethylsiloxane and silicon dioxide, polysiloxane and silica sol dispersed in the dispersing solvent. Taking the total weight of the topcoat coating as 100%, the weight of the conversion product of the polymer of dimethylsiloxane and silicon dioxide, polysiloxane and silica sol accounts for 60%-80% of the total weight of the topcoat coating, and the remainder is the dispersing solvent. That is, the topcoat coating can be a coating in which the conversion product of the polymer of dimethylsiloxane and silicon dioxide, polysiloxane and silica sol is dispersed in a dispersing solvent. Here, the dispersing solvent can be at least one of water and an organic solvent. Here, the organic solvent can be isopropanol, ethanol or propanol. In a preferred embodiment, the organic solvent is isopropanol, because isopropanol can play a better dispersing role in the reaction to be carried out.

[0055] In the above embodiments, the conversion product of polysiloxane and silica sol, the polymer of dimethylsiloxane and silicon dioxide, and the conversion product of polysiloxane and silica sol can ensure the non-stick performance as the top oil layer. In addition, compared with other existing top oil coatings, the modified top oil coating does not contain fillers, pigments and other substances (forming a transparent coating after sintering), and is only a silane material (the conversion product of polysiloxane and silica sol, the polymer of dimethylsiloxane and silicon dioxide, and the conversion product of polysiloxane and silica sol), so it can have improved non-stick properties. In addition, since the modified topcoat paint does not contain fillers, pigments, etc. (these pigments and fillers are powdered inorganic substances and will not participate in the reaction during the formation and maturation process), the formed topcoat layer naturally does not contain powdered inorganic substances such as pigments and fillers embedded in the coating. Therefore, it can have an improved surface density due to the lack of doped particles, and reduce the inducement for the formation of gaps in itself (doped with powdered inorganic substances such as pigments and fillers). Even in the later use process, gaps are not likely to appear or the gaps are not likely to expand further. There will be no part where powdered inorganic substances such as pigments and fillers come into contact with odor molecules and are adsorbed, thereby further reducing the coffee-like odor substances adsorbed in the initial use of the container, avoiding odor residue, and ensuring the durability of the anti-odor performance, thereby enhancing the consumer's experience.

[0056] In addition, the topcoat coating in which the polymer of dimethylsiloxane and silicon dioxide, the conversion product of polysiloxane and silica sol is dispersed in a dispersing solvent can have a relatively small number of hydrogen bond donors. Thus, when used, due to the small number of hydrogen bond donors, the probability of odor substances in beverages (such as odor substances in coffee) combining with the coating surface is reduced, thereby being able to avoid taste residue to a large extent and improving the consumer's experience.

[0057] In addition, it should be noted that the degree of polymerization of the polysiloxane forming the topcoat and the polysiloxane forming the basecoat are different. Specifically, the degree of polymerization of the polysiloxane forming the topcoat is greater than that of the polysiloxane forming the basecoat, so that the topcoat layer has better non-stick properties, while the basecoat layer can be used as a base layer between the container body and the topcoat layer without affecting its bonding strength due to the good non-stick effect. As a specific example, the degree of polymerization of the polysiloxane forming the topcoat is 1700-2100, and the degree of polymerization of the polysiloxane forming the basecoat is 1300-1800.

[0058] According to a second aspect of the present application, a method for preparing a modified ceramic coating is provided, wherein the method for preparing the modified ceramic coating comprises:

[0059] Step S101, forming a mixed slurry including modified polyetheretherketone, polymethylsiloxane and silica sol, wherein the modified polyetheretherketone is at least one of hydroxylated polyetheretherketone and a derivative of hydroxylated polyetheretherketone.

[0060] Step S102 , ripening the mixed slurry to obtain a liquid coating formed by dispersing the reaction product of modified polyetheretherketone, polysiloxane and silica sol in a solvent as a primer coating, thereby preparing a modified ceramic coating.

[0061] According to the preparation method of the modified ceramic coating provided in the embodiment of the present application, in the base oil coating, the modified polyetheretherketone will be formed in the pores of the polymethylsiloxane-silica sol network structure during the sol-gel reaction between polymethylsiloxane and silica sol, and react with polymethylsiloxane, so that the main film-forming substance in the base oil coating (the reaction product of modified polyetheretherketone, polysiloxane and silica sol) is more compact as a whole, thereby improving the density of the formed base oil layer, and the container with the base oil layer is not easy to crack during use, especially not easy to crack the surface oil layer on it due to cracks in itself, so it is not easy to combine with odor molecules, so it can avoid odor residue to a large extent, and improve the consumer's use experience. In addition, the main film-forming substance itself has better heat resistance, so the heat resistance of the base oil layer formed by it can also be improved, so when brewing odorous liquids (for example, brewing coffee), it is not easy to make the base oil layer "heat expand", thereby reducing the possibility of cracks in the base oil layer due to "heat expansion".

[0062] In the embodiments of the present application, the reaction product of modified polyetheretherketone, polysiloxane and silica sol is specifically the reaction product of modified polyetheretherketone, polysiloxane and silica sol reacting in pairs, in other words, it is the reaction product of modified polyetheretherketone, polysiloxane and silica sol combining with each other.

[0063] Hereinafter, the preparation method of the primer coating in the modified ceramic coating according to the present application will be described in conjunction with specific embodiments. Law.

[0064] Modified polyetheretherketone

[0065] According to the present application, the modified polyetheretherketone is specifically a reduction-modified polyetheretherketone or a derivative of the reduction-modified polyetheretherketone. According to some embodiments, the modified polyetheretherketone is at least one of a hydroxylated polyetheretherketone (polyetheretherketone containing a hydroxyl group) and a derivative of a hydroxylated polyetheretherketone. Here, the hydroxylated polyetheretherketone is a compound in which at least part of the carbonyl groups on the surface of the polyetheretherketone are replaced by hydroxyl groups, and the derivative of the hydroxylated polyetheretherketone is a compound in which the carbonyl groups on the surface of the derivative of the polyetheretherketone are replaced by hydroxyl groups.

[0066] According to the present application, the formation method of the modified polyetheretherketone includes reducing the carbonyl group on the surface of polyetheretherketone (PEEK) to hydroxyl group using a strong reducing agent. Here, the strong reducing agent can be lithium aluminum hydride or sodium borohydride, which can realize the conversion of ketone (compound containing carbonyl group C=O) to hydroxyl group (-OH), thereby obtaining the modified polyetheretherketone. In a preferred embodiment, the strong reducing agent is preferably sodium borohydride, and sodium borohydride NaBH 4 to provide electrons, which can dissociate H under mild conditions - ions, these H - The ion has strong nucleophilicity and can undergo nucleophilic addition reaction to positively charged centers. - The ions can directly donate electrons to reduce the carbonyl group to a hydroxyl group.

[0067] In order to make the reduction reaction proceed smoothly, a suitable solvent and an appropriate reaction temperature can be selected. As an example, the solvent can be dimethyl sulfoxide (DMSO), which as a non-polar solvent has a good affinity with the surface of the PEEK material, and the reaction temperature is 100°C-120°C. NaBH 4 The solubility in DMSO reaches the maximum, which is conducive to the reduction reaction.

[0068] In these embodiments, compared with polyetheretherketone, the modified polyetheretherketone has a hydroxyl group that can react with polymethylsiloxane, and can be grafted onto polymethylsiloxane and silica sol during the reaction of polymethylsiloxane and silica sol to form a network structure, so as to form a main film-forming substance together. In addition, the modified polyetheretherketone has good hydrophilicity during the preparation of the primer coating, which is beneficial to its solubility in the mixed slurry.

[0069] Forming mixed slurry

[0070] According to the present application, forming a mixed slurry including modified polyetheretherketone, polymethylsiloxane and silica sol includes stirring and mixing the modified polyetheretherketone, polymethylsiloxane and silica sol to obtain a mixed slurry. In the mixed slurry, based on 100 parts of the total weight of the mixed slurry, the weight part of the modified polyetheretherketone is 0.1 parts to 0.5 parts, the weight part of the polymethylsiloxane is 30 parts to 40 parts, and the weight part of the silica sol is 10 parts to 15 parts.

[0071] In these embodiments, the modified polyetheretherketone, polysiloxane and silica sol in the mixed slurry have suitable weight proportions, which can facilitate the formation of the main film-forming substance (the reaction product of modified polyetheretherketone, polysiloxane and silica sol) after ripening and in the process of forming the modified ceramic coating, thereby improving the anti-odor performance while ensuring the non-stickiness of the modified ceramic coating.

[0072] In some embodiments, the step of forming a mixed slurry including modified polyetheretherketone, polysiloxane and silica sol includes: mixing the modified polyetheretherketone and silica sol, adjusting the pH value to 3-6, and then adding polysiloxane to form a mixed slurry including polyetheretherketone, polysiloxane and silica sol. In the present application, the pH value can be adjusted with at least one organic acid selected from formic acid and acetic acid. Specifically, the modified polyetheretherketone, silica sol and organic acid are mixed and stirred for 0.5h-2h to fully mix the modified polyetheretherketone, silica sol and organic acid, and then polysiloxane is added and stirred to roll and mix for 4h-10h, so that the polysiloxane reacts with the silica sol and the modified polyetheretherketone under acidic conditions.

[0073] In some embodiments, the step of maturing the mixed slurry includes: stirring the mixed slurry at a temperature of 15°C-25°C for 4h-10h and maintaining the pH value to 3-6 to mature the mixed slurry, which can be more conducive to the formation of a reaction product of modified polyetheretherketone, polysiloxane and silica sol.

[0074] In some embodiments, the mixed slurry also includes pigments and fillers and solvents, wherein the weight of the pigments and fillers is 20-30 parts, and the weight of the solvent is 10-30 parts, based on the total weight of the mixed slurry as 100 parts. Here, the pigments and fillers may include pigments and / or fillers. The pigment is used to provide the color of the base oil layer, and the filler is used to provide the hardness, strength, etc. of the base oil layer. As a specific example, the pigment may be titanium dioxide. The filler may be at least one of bentonite and kaolin. In the case where the pigment and filler include pigments and fillers, the weight ratio of the pigment to the filler may be 1:5-2:1. The solvent may be at least one of water and an organic solvent, wherein the organic solvent may include isopropanol and ethanol. In the case where the solvent includes water and an organic solvent, the present application does not limit the mixing ratio of the two.

[0075] Hereinafter, a method for preparing the top oil coating in the modified ceramic coating according to the present application will be described in conjunction with specific embodiments.

[0076] According to the present application, the modified ceramic coating can be a dual-system coating, that is, the ceramic coating includes a primer coating and a topcoat coating that are used independently and placed separately. The dual-system coating will first form a base oil layer through the primer coating, and then form a topcoat layer on the primer layer through the topcoat coating. The addition of the topcoat layer can further seal the cracks in the base oil layer due to, for example, high temperature during use, that is, further reduce the possibility of cracks on the exposed surface of the ceramic coating that can be combined with odor molecules.

[0077] According to the present application, the base oil coating is the base oil coating provided in the above embodiment. The top oil coating can be an existing top oil coating, and preferably, the top oil coating can be a modified top oil coating.

[0078] In some preferred embodiments according to the present application, the topcoat may be a modified topcoat. As some examples, the modified topcoat includes a dispersion solvent and a conversion product of polysiloxane and silica sol dispersed in the dispersion solvent. The corresponding method for preparing the modified topcoat includes forming a dispersion including polysiloxane, forming a dispersion including silica sol, and mixing the dispersion of polysiloxane and the dispersion of silica sol to form the modified topcoat. As other examples, the modified topcoat includes a dispersion solvent and a polymer of dimethylsiloxane and silica dispersed in the dispersion solvent, and a conversion product of polysiloxane and silica sol. The corresponding method for preparing the modified topcoat includes forming a dispersion including polysiloxane, forming a dispersion including silica sol, and forming a dispersion including a polymer of dimethylsiloxane and silica, and mixing the dispersion of polysiloxane, the dispersion of silica sol, and the dispersion of the polymer of dimethylsiloxane and silica to form the modified topcoat.

[0079] The preparation method of the modified topcoat of the present application will be specifically described below by taking the modified topcoat including a dispersing solvent and a polymer of dimethylsiloxane and silicon dioxide, a polysiloxane and a conversion product of silica sol dispersed in the dispersing solvent as an example.

[0080] According to the present application, a method for preparing a modified top oil coating is provided, wherein the method for preparing the modified top oil coating comprises:

[0081] Step S201, forming a mixed slurry including a polymer of dimethylsiloxane and silicon dioxide, polymethylsiloxane and silica sol, wherein the weight ratio of polymethylsiloxane, silica sol and the polymer of dimethylsiloxane and silicon dioxide is (25-30):(5-10):(30-40).

[0082] Step S202, stirring and mixing the mixed slurry to obtain a matured modified topcoat coating as the topcoat coating of the present application.

[0083] According to the method for preparing a modified topcoat provided in an embodiment of the present application, a modified topcoat is obtained by mixing and aging a mixed slurry including a polymer of dimethylsiloxane and silicon dioxide, polymethylsiloxane and silica sol. Compared with existing topcoats, the coating formed by the modified topcoat obtained by mixing and aging the above raw materials can provide a relatively small number of hydrogen bond donors. Thus, when used, due to the small number of hydrogen bond donors, the probability of odor substances in the beverage (such as odor substances in coffee) binding to the coating surface is reduced, thereby being able to avoid taste residue to a large extent and improving the consumer's experience.

[0084] Hereinafter, the method for preparing the modified top oil coating according to the present application will be described in combination with specific steps.

[0085] Forming mixed slurry

[0086] According to the present application, the polysiloxane is one of polymethylsiloxane, polymethylphenylsiloxane and polyethylsiloxane, and the raw materials for forming the modified topcoat coating include commercially available liquid silica sol. In some embodiments, the polymethylsiloxane is selected to have a viscosity in the range of 6 seconds to 12 seconds using the Iwata No. 2 cup test. In the topcoat layer, most of the polymethylsiloxane will hydrolyze to form a network structure. The polymethylsiloxane has improved non-stickiness (provided by the methyl group), and the network structure formed by it is easy to lock the silicon dioxide molecules generated by the silica sol, that is, the silicon dioxide molecules generated by the silica sol are easy to fill into the network structure to form the overall main film-forming material skeleton.

[0087] In addition, among the raw materials in the modified topcoat paint, the weight proportion of polymethylsiloxane is relatively small, and it should not be too much or too little. If the weight proportion of the raw material polymethylsiloxane in the modified topcoat paint is too much, there will be more hydroxyl groups in the formed coating, which can serve as hydrogen bond donors. In this case, it will be detrimental to the purpose of reducing the hydrogen bond donors in the coating of this application. If the weight proportion of the raw material polymethylsiloxane in the modified topcoat paint is too little, it will affect the performance of the formed coating, for example, water resistance, weather resistance, hardness and other properties will be reduced.

[0088] According to the present application, the reaction product of dimethyl (siloxane and polysiloxane) and silicon dioxide, also known as the polymer of dimethyl siloxane and silicon dioxide, i.e., CAS: 67762-90-7, has hydrophobicity, chemical stability and mechanical strength, and can embed silane functional groups on the surface of silicon dioxide formed by silica sol, thereby generating a layer of stable chemically bonded silane product. Here, the polymer of dimethyl siloxane and silicon dioxide can be obtained commercially, or it can be prepared by the following preparation method. As an example, dimethyl siloxane and chlorosilane [such as trichlorosilane (SiHCl 3 ), trichloromethylsilane (CH 3 SiCl 3 ) etc.] are subjected to hydrolysis reaction under the catalysis of hydrochloric acid to obtain a polymer of dimethylsiloxane and silicon dioxide.

[0089] According to the present application, the polymer of dimethylsiloxane and silicon dioxide provides non-stickiness (methyl group provides) on the one hand, and can hydrolyze with silica sol to form SiO 2 The reaction ensures the integrity of the modified top oil coating, and does not introduce hydrogen bond donors. At the same time, it can reduce the brittleness of the formed modified ceramic coating to improve the strength, and has a good bonding force with the base oil layer, thereby improving the overall strength of the modified ceramic coating.

[0090] It should be noted that the mixed slurry may also include raw materials such as solvents. The solvent is used to adjust the viscosity of the modified topcoat paint so that the paint can be better applied and coated on the surface of the cup base. The filler is used to adjust the appearance of the final coating product. As an example, the solvent can be isopropyl alcohol, purified water or ethanol.

[0091] According to the present application, after preparing the various raw materials, they are mixed. Specifically, a mixed slurry including a polymer of dimethylsiloxane and silicon dioxide, polymethylsiloxane and silica sol is formed, which includes mixing the polymer of dimethylsiloxane and silicon dioxide and silica sol, and then adding polymethylsiloxane to form a mixed slurry including a polymer of dimethylsiloxane and silicon dioxide, polymethylsiloxane and silica sol.

[0092] In these embodiments, first, the polymer of dimethylsiloxane and silica and the silica sol are mixed evenly to ensure that the two components are evenly distributed in the system. The silica sol can act as a crosslinking agent here, and can undergo a condensation reaction with the hydroxyl groups in the polymer of dimethylsiloxane and silica to form a preliminary crosslinked network. Next, polymethylsiloxane is added. At this time, since the reaction activity between polymethylsiloxane and silica sol is higher than the reaction activity with the polymer of dimethylsiloxane and silica, polymethylsiloxane will preferentially react with silica sol to further expand and strengthen the crosslinked network. This reaction may involve condensation between the methyl groups in polymethylsiloxane and the hydroxyl groups in silica sol to form a more stable silicon-oxygen-silicon bond. Through this step-by-step mixing and reaction method, a more uniform and dense crosslinked network can be formed, thereby improving the strength, durability and other physical properties of the coating. In addition, this method also helps to control the reaction rate and reduce the generation of by-products, thereby optimizing the overall performance of the product.

[0093] According to the present application, during the mixing process, the pH value of the mixed slurry system is maintained in the range of 5-7 and the temperature is 20°C-30°C. Under these conditions, the formation of the matured modified topcoat can be promoted.

[0094] According to the present application, in the stirring and mixing step, the temperature in the mixing step is controlled to be 20°C-30°C, and the mixing time is 8h-12h. Specifically, the mixed slurry is added to a mixing device, and the temperature of the mixing device and the stirring device of the mixing device are controlled so that the mixed slurry is mixed and stirred for 8h-12h at a temperature of 20°C-30°C to ensure that the components in the coating are fully mixed. During the mixing process, dimethylsiloxane interacts with silicon dioxide polymers, polymethylsiloxane and silica sol to form reaction products. In the subsequent sintering stage after the coating is formed, the reaction products are cross-linked with each other to form a modified topcoat coating according to the present application that is not easy to form hydrogen bonds with other substances. The topcoat layer formed by the modified topcoat coating not only has excellent anti-odor performance, but also has excellent physical properties, such as strength, hardness and wear resistance.

[0095] According to the present application, the mixed slurry includes a polymer of dimethylsiloxane and silicon dioxide, polymethylsiloxane and silica sol, wherein, in parts by weight, the weight of polymethylsiloxane is 3-5 parts, the weight of silica sol is 20-35 parts, and the weight of the polymer of dimethylsiloxane and silicon dioxide is 20-35 parts. In some embodiments, the mixed slurry also includes titanium dioxide, pigment brown and solvent, wherein the weight of titanium dioxide is 10-20 parts, the weight of pigment brown is 1-2 parts, and the weight of solvent is 10-30 parts.

[0096] In these embodiments, titanium dioxide is usually white, and pigment brown is usually black. By setting the two to have a suitable weight ratio, a modified topcoat coating of a desired color can be formed, thereby obtaining a coating of a cup with a desired color. The modified topcoat coating formed by the mixed slurry of the above multiple components after aging can ensure that the modified topcoat coating has a suitable viscosity, avoid sagging when spraying to form the coating, and ensure the quality of the coating. In addition, the stability and uniformity of the formed modified topcoat coating can also be ensured.

[0097] Curing is a key step in the preparation of ceramic coatings, which involves chemical reactions and physical changes of various components in the coating to form a stable coating system. In this process, pH value and stability are two very important parameters, which directly affect the quality and performance of the coating.

[0098] Specifically, the molecular formula of silica sol can be written as Si(OH) 4 , -OH, also known as hydroxyl, during the sintering process, silica sol will decompose into SiO 2 , polymethylsiloxane and silicon dioxide react to form a silicon dioxide polymer with methyl groups, and when the polymer of dimethylsiloxane and silicon dioxide and silicon dioxide are mixed and reacted under the action of temperature, the hydroxyl groups on the surface of the silica sol will chemically react with the methyl groups on the molecular chain of the polymer of dimethylsiloxane and silicon dioxide to form a binary cross-linked structure. That is, after sintering, a modified ceramic coating with the conversion product of the polymer of dimethylsiloxane and silicon dioxide, polymethylsiloxane and silica sol combined with each other as the main component can be formed.

[0099] As a specific example, the topcoat coating in which the conversion product of dimethylsiloxane and silicon dioxide polymer, polysiloxane and silica sol is dispersed in a dispersion solvent is prepared by ripening a mixed slurry including dimethylsiloxane and silicon dioxide polymer, polysiloxane and silica sol. As a specific example, in the mixed slurry, based on 100 parts by weight, the weight of polymethylsiloxane is 25-30 parts, the weight of silica sol is 5-10 parts, the weight of dimethylsiloxane and silicon dioxide polymer is 30-40 parts, and the balance is the dispersion solvent.

[0100] In some embodiments, the modified topcoat coating is a coating comprising a conversion product of a polymer of dimethylsiloxane and silica, a polymethylsiloxane and a silica sol. As an example, in the modified topcoat coating, the conversion product may include a bonding product of polymethylsiloxane and silica sol, a bonding product of dimethylsiloxane and a polymer of silica and a silica sol, a bonding product of dimethylsiloxane and a polymer of silica and polymethylsiloxane, and a bonding product of polymethylsiloxane, a silica sol, and a polymer of dimethylsiloxane and silica. According to the present application, different combinations of bonding products can provide different properties and characteristics for the coating, so that it can adapt to a wider range of application scenarios and more stringent use requirements. As an example, the bonding product of polymethylsiloxane and silica sol can provide a certain degree of non-stickiness, so that the cups with the modified ceramic coating have easy-to-clean properties. The bonding product of dimethylsiloxane, silicon dioxide polymer and silica sol has wear resistance, so that the cups with the modified ceramic coating have good stability and durability.

[0101] In these embodiments, after aging, the modified topcoat coating has a certain amount of dimethylsiloxane and silicon dioxide polymer, polysiloxane and silica sol conversion products as the main film-forming substances. Here, the dimethylsiloxane and silicon dioxide polymer, polysiloxane and silica sol conversion products are specifically products of dimethylsiloxane and silicon dioxide polymer, polysiloxane and silica sol combined with each other through chemical reactions. When the modified topcoat coating is sprayed to form a modified ceramic coating, as the solvent and the like volatilize, the reaction products in the modified topcoat coating are further cross-linked to form a large amount of cross-linked products including dimethylsiloxane and silicon dioxide polymer, polysiloxane and silica sol combined with each other as the topcoat layer of the container. The topcoat layer is dense and not easy to crack, so it can serve as a protective layer for the bottomcoat layer and can inhibit cracks in the bottomcoat layer, so that the container is not easy to retain odor during use, further improving the consumer's experience.

[0102] In some embodiments, based on the total weight of the modified topcoat coating being 100%, the weight of the conversion product in the modified topcoat coating accounts for 60% to 80% of the total weight of the modified topcoat coating.

[0103] In these embodiments, the modified topcoat coating contains 60%-80% by weight of the conversion product, and the remainder is a dispersing solvent, which can ensure that the cup is non-stick and further enhance the consumer's experience.

[0104] According to the third aspect of the present application, a modified ceramic coating is provided, which is at least used in cups, wherein the modified ceramic coating comprises a cross-linked product layer of a reaction product of modified polyetheretherketone, polysiloxane and silica sol as a primer layer, wherein the cross-linked product layer of a reaction product of modified polyetheretherketone, polysiloxane and silica sol is a cross-linked product layer formed by dehydration condensation of a primer coating having a reaction product of modified polyetheretherketone, polysiloxane and silica sol in a sintering stage after spraying. The modified polyetheretherketone is at least one of a hydroxylated polyetheretherketone and a derivative of a hydroxylated polyetheretherketone.

[0105] According to the modified ceramic coating provided in the embodiment of the present application, a cross-linked product layer of the reaction product of modified polyetheretherketone, polysiloxane and silica sol is used as the base oil layer. The coating is dense and not prone to cracks during use, and is not easy to combine with odor molecules. Therefore, it can avoid odor residue to a large extent and enhance the consumer's experience.

[0106] In some embodiments, in the primer coating, the reaction products of modified polyetheretherketone, polysiloxane and silica sol as the main film-forming substances form a network structure. In the primer layer, the main film-forming substances of the network structure can form a dense primer layer, thereby further avoiding residual taste and enhancing the consumer's experience.

[0107] According to the present application, the base oil layer includes not only a cross-linked product layer of the reaction product of modified polyetheretherketone, polysiloxane and silica sol, but also pigments and fillers dispersed in the liquid coating. As an example, taking the total weight of the base oil layer as 100%, the weight of the cross-linked product layer of the reaction product of modified polyetheretherketone, polysiloxane and silica sol accounts for 60% to 70% of the total weight of the base oil layer, and the weight of the pigments and fillers accounts for 30% to 40% of the total weight of the base oil layer. In this way, the strength of the base oil layer can be optimized while ensuring the compactness of the base oil layer, thereby suppressing base oil cracks to further avoid taste residue and enhance the consumer's experience.

[0108] In some embodiments, the thickness of the base oil layer is 10 μm-30 μm, so that the life of the base oil layer can be guaranteed.

[0109] In some embodiments, the color filler includes pigments and fillers, the pigment includes at least one of titanium dioxide, carbon black, copper chrome black, iron oxide, pigment brown and pigment orange, and the filler includes at least one of bentonite, kaolin, mica powder, montmorillonite, silicon carbide, alumina and silicon dioxide. In this way, the strength of the base oil layer can be optimized while ensuring the density of the base oil layer, thereby inhibiting base oil cracks to further avoid residual taste, and the color of the base oil layer can be ensured to enhance the consumer's usage experience.

[0110] In some embodiments, the weight ratio of the pigment to the filler is 1:2-2:1. The pigment and the filler have a suitable weight ratio, which can take into account both strength improvement and color improvement to a certain extent without excessively affecting the density of the base oil layer.

[0111] In some embodiments, the modified ceramic coating further comprises a top oil layer disposed on the base oil layer, specifically, a top oil layer covering the base oil layer, the top oil layer being a crosslinked product layer of a conversion product of polysiloxane and silica sol, i.e., a layer formed by crosslinking the conversion product of polysiloxane and silica sol. Alternatively, the top oil layer is a crosslinked product layer of a conversion product of dimethylsiloxane and a polymer of silicon dioxide, polysiloxane, silica sol, and, i.e., a layer formed by crosslinking the conversion product of dimethylsiloxane and a polymer of silicon dioxide, polysiloxane, silica sol, and.

[0112] In these embodiments, the modified ceramic coating has a double-layer structure, which can further enhance the advantages of the primer-modified polyetheretherketone. When there is no modified polyetheretherketone in the primer, thermal expansion will cause gaps in the primer, and cracks may also appear in the thinner top oil, which cannot block the gaps. When the primer contains modified polyetheretherketone, high-temperature thermal expansion has no obvious effect on the cracks in the coating, and the small gaps in the primer can be further sealed after the top oil is applied.

[0113] In some embodiments, the thickness of the surface oil layer is 1 μm-5 μm, so that the life of the surface oil layer can be guaranteed.

[0114] According to a fourth aspect of the present application, a method for manufacturing a container is provided, wherein the method for manufacturing the container comprises spraying a primer coating on a container body to form a primer layer, and spraying a topcoat coating on the primer layer to form a topcoat layer.

[0115] According to the present application, a primer coating is sprayed on the container body to form a primer layer, wherein the spraying can be air spraying, and as an example, the parameters of air spraying include: a spraying distance of 140mm-180mm; an air pressure of 0.2MPa-0.4MPa; a flow rate of 5L / min-10L / min; a moving speed of the spray gun of 30cm / second-60cm / second; an angle between the gun nozzle and the sprayed object of 80°-100°; a moving speed of the spray gun of 30cm / second-60cm / second; and a spray gun caliber of 1.4mm-1.6mm. The primer coating is a liquid coating, so it can be evenly distributed on the surface of the container body and is easy to apply.

[0116] According to the present application, a topcoat is sprayed on the base oil layer to form a topcoat layer, wherein the spraying can be air spraying, and as an example, the parameters of air spraying include: a spraying distance of 140mm-180mm; an air pressure of 0.2MPa-0.4MPa; a flow rate of 5L / min-10L / min; a moving speed of the spray gun of 30cm / second-60cm / second; an angle between the gun nozzle and the sprayed object of 80°-100°; a moving speed of the spray gun of 30cm / second-60cm / second; and a spray gun caliber of 1.4mm-1.6mm. The topcoat is a liquid coating, so it can be evenly distributed on the surface of the base oil layer and is easy to apply.

[0117] According to the present application, after spraying, a step of curing the modified ceramic coating sprayed by air is also included. As an example, the coating can be cured by sintering. Specifically, the sintering temperature is 200°C-300°C and the sintering time is 8-15 minutes to improve the overall quality of the modified ceramic coating.

[0118] Under the influence of sintering temperature, the solvent in the modified ceramic coating sprayed by air is volatilized. When the solvent is reduced, most of the polyetheretherketone, polymethylsiloxane and silica sol in the modified ceramic coating are cross-linked with each other at this stage to form a modified ceramic coating including a cross-linked product of the reaction products of the three as a base oil layer. In this way, the anti-odor performance of the cups with the modified ceramic coating can be further optimized.

[0119] According to a fourth aspect of the present application, a container is provided, wherein the container comprises a container body and a modified ceramic coating formed on the inner wall surface of the container body, wherein the modified ceramic coating is the modified ceramic coating described above; or, a layer formed by the modified ceramic coating modified ceramic coating, wherein the modified ceramic coating is the modified ceramic coating described above or is a ceramic coating formed according to the method for preparing the modified ceramic coating described above.

[0120] In some embodiments, the container is a container with anti-odor requirements, and can be specifically a cup, a pot, or the inner liner of a pot. Here, the pot includes a frying pan, a wok, or the inner liner of a pot.

[0121] Taking a cup as an example, the cup includes a cup body, and the modified ceramic coating is formed on the inner wall of the cup body. Here, the cup body can be a stainless steel body, specifically 304 stainless steel or 316 stainless steel.

[0122] Hereinafter, the beneficial effects of the inventive concept will be described in conjunction with specific examples.

[0123] Example 1

[0124] The base coat is formed by the following method.

[0125] S10, forming a mixed slurry including modified polyetheretherketone, polymethylsiloxane, silica sol and isopropyl alcohol (solvent). In the mixed slurry, in parts by weight, the modified polyetheretherketone is 0.3 parts by weight, the polymethylsiloxane is 35 parts by weight, the silica sol is 13 parts by weight, and the isopropyl alcohol is 20 parts by weight.

[0126] The mixed slurry was stirred and mixed at a temperature of 25° C. for 10 hours, and the pH value of the system was maintained at 3-6 to obtain a matured coating, thereby forming a primer coating.

[0127] The anti-odor cup is manufactured by using the above-mentioned base oil coating through the following method.

[0128] S20: providing a cup body.

[0129] S30: Preheating: Clean the cup body and preheat it to 60°C.

[0130] S40: Spraying. A primer layer with a thickness of 20 microns is formed on the inner surface of the cup body by air spraying using a primer coating as a modified ceramic coating for the cup. The spray gun caliber is 1.0 mm, and the air spraying parameters are as follows: the spraying distance is 160 mm; the air pressure is 0.3 MPa, the flow rate is 7 L / min; the moving speed of the spray gun is 40 cm / s; and the angle between the gun nozzle and the sprayed object is 90°.

[0131] S50: Sintering. Curing at 280°C for 10 minutes.

[0132] Through the above method, the anti-odor cup of Example 1 is obtained.

[0133] Example 2

[0134] The anti-odor cup of Example 2 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.1 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0135] Example 3

[0136] The anti-odor cup of Example 3 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.5 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0137] Example 4

[0138] The anti-odor cup of Example 4 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 30 parts, the weight portion of silica sol was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0139] Example 5

[0140] The anti-odor cup of Example 5 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 40 parts, the weight portion of silica sol was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0141] Example 6

[0142] The anti-odor cup of Example 6 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 10 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0143] Example 7

[0144] The anti-odor cup of Example 7 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 15 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0145] Example 8

[0146] The anti-odor cup of Example 8 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylphenylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0147] Example 9 (The following is an example corresponding to the base oil including filler and titanium dioxide)

[0148] The anti-odor cup of Example 9 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0149] Example 10

[0150] The anti-odor cup of Example 10 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.1 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0151] Embodiment 11

[0152] The anti-odor cup of Example 11 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.5 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0153] Example 12

[0154] The anti-odor cup of Example 12 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 30 parts, the weight portion of silica sol was 13 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0155] Example 13

[0156] The anti-odor cup of Example 13 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 40 parts, the weight portion of silica sol was 13 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0157] Embodiment 14

[0158] The anti-odor cup of Example 14 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 10 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0159] Embodiment 15

[0160] The anti-odor cup of Example 15 was manufactured by the same method as Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylsiloxane was 35 parts, the weight portion of silica sol was 15 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0161] Example 16

[0162] The anti-odor cup of Example 16 was manufactured in the same manner as in Example 1, except that different weight portions of raw materials were used to form the primer coating in step S10 (wherein, in parts by weight, the weight portion of modified polyetheretherketone was 0.3 parts, the weight portion of polymethylphenylsiloxane was 35 parts, the weight portion of silica sol was 13 parts, the weight portion of titanium dioxide was 13 parts, the weight portion of bentonite was 13 parts, and the weight portion of isopropyl alcohol was 20 parts).

[0163] Example 17 (the following is an example of adding a surface oil layer to Example 1)

[0164] The anti-odor cup of Example 17 was manufactured by the same method as in Example 1, except that a top oil layer with a thickness of 3 μm was formed on the base oil layer of Example 1 between step S40 and step S50 of Example 1 using a top oil coating (the top oil coating includes dispersed isopropyl alcohol and conversion products of polysiloxane and silica sol dispersed in isopropyl alcohol, and the weight of the conversion products of polysiloxane and silica sol accounts for 70% of the total weight of the top oil coating based on the total weight of the top oil coating being 100%, and the balance being isopropyl alcohol).

[0165] Embodiment 18

[0166] The anti-odor cups of Example 18 were manufactured by the same method as in Example 1, except that a top oil layer with a thickness of 3 μm was formed on the base oil layer of Example 1 between step S40 and step S50 of Example 1. The top oil coating comprises isopropyl alcohol and a polymer of dimethylsiloxane and silicon dioxide, a conversion product of polysiloxane and silica sol dispersed in isopropyl alcohol, and the weight of the conversion product of the polymer of dimethylsiloxane and silicon dioxide, polysiloxane and silica sol accounts for 70% of the total weight of the top oil coating based on the total weight of the top oil coating as 100%, and the balance is isopropyl alcohol.

[0167] Example 19 (The following is an example of adding a surface oil layer to Example 9)

[0168] The anti-odor cups of Example 19 were manufactured by the same method as in Example 9, except that a top oil layer with a thickness of 3 μm was formed on the base oil layer of Example 9 between step S40 and step S50 of Example 9 using a top oil coating (the top oil coating includes isopropyl alcohol and conversion products of polysiloxane and silica sol dispersed in isopropyl alcohol, and the weight of the conversion products of polysiloxane and silica sol accounts for 70% of the total weight of the top oil coating based on the total weight of the top oil coating being 100%, and the balance being isopropyl alcohol).

[0169] Embodiment 20

[0170] The anti-odor cups of Example 20 were manufactured in the same manner as in Example 9, except that a top oil layer with a thickness of 3 μm was formed on the base oil layer of Example 9 between step S40 and step S41 of Example 9 using a top oil coating (the top oil coating includes isopropyl alcohol and a polymer of dimethylsiloxane and silicon dioxide, a polysiloxane and a conversion product of silica sol dispersed in isopropyl alcohol, and the weight of the conversion product of the polymer of dimethylsiloxane and silicon dioxide, a polysiloxane and a silica sol accounts for 70% of the total weight of the top oil coating based on the total weight of the top oil coating as 100%, and the remainder is isopropyl alcohol).

[0171] Comparative Example 1

[0172] The anti-odor cup of Comparative Example 1 was manufactured in the same manner as in Example 1, except that a different primer coating was used instead of the primer coating of Example 1 in step S10 (the primer coating of Comparative Example 1 was a primer coating matured from polymethylsiloxane, silica sol and isopropyl alcohol, and in the primer coating, the weight parts of polymethylsiloxane were 35 parts, the weight parts of silica sol were 13 parts, and the weight parts of isopropyl alcohol were 20 parts).

[0173] Comparative Example 2

[0174] The anti-odor cups of Comparative Example 2 were manufactured in the same manner as in Example 9, except that a different primer was used in place of the primer of Example 9 in step S10 (the primer of Comparative Example 2 was a primer of polymethylsiloxane, silica sol, titanium dioxide, bentonite and isopropyl alcohol matured, in which the weight proportion of polymethylsiloxane, silica sol, titanium dioxide, bentonite and isopropyl alcohol was 35 parts, 13 parts, 13 parts, 13 parts, and 20 parts, respectively).

[0175] Comparative Example 3

[0176] The anti-odor cups of Comparative Example 3 were manufactured in the same manner as in Example 1, except that a different primer coating was used in place of the primer coating of Example 1 in step S10 (the primer coating of Comparative Example 1 was a primer coating matured from polymethylphenylsiloxane, silica sol and isopropyl alcohol, and in the primer coating, the weight parts of polymethylphenylsiloxane were 35 parts, the weight parts of silica sol were 13 parts, and the weight parts of isopropyl alcohol were 20 parts).

[0177] Comparative Example 4

[0178] The anti-odor cups of Comparative Example 4 were manufactured in the same manner as in Example 9, except that a different primer coating was used in place of the primer coating of Example 9 in step S10 (the primer coating of Comparative Example 2 was a primer coating of polymethylphenylsiloxane, silica sol, titanium dioxide, bentonite and isopropyl alcohol matured, in which the weight parts of polymethylphenylsiloxane, silica sol, titanium dioxide, bentonite and isopropyl alcohol were 35 parts, 13 parts, 13 parts, 13 parts, and 20 parts, respectively).

[0179] The non-stick properties of the anti-odor cups of Examples 1-20 and Comparative Examples 1-4 were tested, and the test results are shown in Table 1 below.

[0180] The performance index test method is as follows:

[0181] (1) Odor test method:

[0182] 1. Brew coffee (15g coffee + 150ml water), pour out the coffee after soaking for a period of time, wash and smell it, and then continue soaking.

[0183] 2. Evaluation: Grade A (no odor); Grade B (slight odor, acceptable); Grade C (obvious odor, unacceptable);

[0184] 3. Test the odor every 1 hour and record the time it takes for the cup to reach Class C. The longer the time, the better the anti-odor effect of the tested anti-odor cup.

[0185] (2) Cleanability test method:

[0186] 1. Wash the cups in the dishwasher for 5 consecutive times (each time for 1.5 hours).

[0187] 2. Spread the ketchup evenly on the bottom of the cup and leave it for 2 hours.

[0188] 3. Rinse with tap water and check for stains and stains that are difficult to clean.

[0189] 4. Evaluation method: Grade A (no difficult-to-clean stains and stains after rinsing); Grade B (there are difficult-to-clean stains, but no stains); Grade C (there are stains remaining).

[0190] 5. The above is one cycle. Record the number of cycles to reach Class C. The greater the number of cycles, the easier it is to clean the odor-proof cup.

[0191] (3) Impact resistance test method: Use a 50g steel ball to drop freely from a certain height to hit the bottom of a water cup coated with a ceramic coating, and record the height at which the collapse occurs. The higher the height, the higher the coating strength of the anti-odor cup being tested.

[0192] Table 1 Test result record

[0193]

[0194] By comparing and analyzing the embodiments 1-20 and comparative examples 1-4 of the present invention, it can be seen that compared with the cups with ceramic coating formed by conventional ceramic coatings, the cups formed by the modified ceramic coatings including modified polyetheretherketone, polymethylsiloxane and silica sol according to the present application can be used for a long time without odor, and are easy to clean, and the user experience is good. In addition, the cups formed by the modified ceramic coatings have good impact resistance and have a high bonding strength with the cup body, so that the overall strength of the cups is better.

[0195] Although the embodiments of the present application have been described in detail above, those skilled in the art may make various modifications and variations to the embodiments of the present application without departing from the spirit and scope of the present application. However, it should be understood that, in the opinion of those skilled in the art, these modifications and variations will still fall within the spirit and scope of the embodiments of the present application defined by the claims.

Claims

1. A modified ceramic coating, characterized in that: The modified ceramic coating uses a liquid coating formed by dispersing a reaction product of modified polyetheretherketone, polysiloxane and silica sol in a solvent as a base oil coating, wherein the modified polyetheretherketone is at least one of hydroxylated polyetheretherketone and a derivative of hydroxylated polyetheretherketone.

2. The modified ceramic coating according to claim 1, characterized in that: Taking the total weight of the base oil coating as 100%, the weight of the reaction product accounts for 40% to 55% of the total weight of the base oil coating, and the remainder is the solvent.

3. The modified ceramic coating according to claim 1, characterized in that: The base oil coating also includes pigments and fillers dispersed in the liquid coating. Taking the total weight of the base oil coating as 100%, the weight of the reaction product accounts for 40% to 55% of the total weight of the base oil coating, the weight of the pigments and fillers accounts for 20% to 30% of the total weight of the base oil coating, and the remainder is solvent.

4. The modified ceramic coating according to claim 1, characterized in that: The reaction product has a network structure.

5. The modified ceramic coating according to claim 1, characterized in that: The polysiloxane includes at least one of polymethylsiloxane, polymethylphenylsiloxane and polyethylsiloxane.

6. The modified ceramic coating according to claim 1, characterized in that: The modified ceramic coating also includes a topcoat coating, which is placed separately from the basecoat coating, wherein the topcoat coating includes a dispersion solvent and a siloxane polymer dispersed in the dispersion solvent; wherein the siloxane polymer includes a conversion product of polysiloxane and silica sol, or includes a polymer of dimethylsiloxane and silicon dioxide, and a conversion product of polysiloxane and silica sol.

7. The modified ceramic coating according to claim 6, characterized in that: In the case where the siloxane polymer includes a conversion product of polysiloxane and silica sol, based on the total weight of the topcoat coating being 100%, the weight of the conversion product of polysiloxane and silica sol accounts for 60%-80% of the total weight of the topcoat coating, and the remainder is a dispersing solvent; or In the case where the silicone polymer includes a polymer of dimethylsiloxane and silicon dioxide, a conversion product of polysiloxane and silica sol, based on the total weight of the topcoat coating being 100%, the weight of the conversion product of dimethylsiloxane and silicon dioxide, polysiloxane and silica sol accounts for 60%-80% of the total weight of the topcoat coating, and the remainder is a dispersing solvent.

8. A method for preparing a modified ceramic coating, characterized in that: The preparation method of the modified ceramic coating comprises the following steps: forming a mixed slurry comprising modified polyetheretherketone, polysiloxane and silica sol, wherein the modified polyetheretherketone is at least one of hydroxylated polyetheretherketone and a derivative of hydroxylated polyetheretherketone; The mixed slurry is aged to obtain a liquid coating formed by dispersing a reaction product of modified polyetheretherketone, polysiloxane and silica sol in a solvent as a primer coating, thereby preparing the modified ceramic coating.

9. The method for preparing the modified ceramic coating according to claim 8, characterized in that: In the mixed slurry, the weight ratio of the modified polyetheretherketone, the polysiloxane and the silica sol is (0.1-0.5):(30-40):(10-15).

10. The method for preparing the modified ceramic coating according to claim 8, characterized in that: The forming step comprises a mixed slurry of modified polyetheretherketone, polysiloxane and silica sol, comprising: The modified polyetheretherketone and silica sol are mixed, and the pH value is adjusted to 3-6, and then the polysiloxane is added to form a mixed slurry including polyetheretherketone, polysiloxane and silica sol.

11. The method for preparing the modified ceramic coating according to claim 8, characterized in that: The step of ripening the mixed slurry comprises: stirring the mixed slurry for 4 hours to 10 hours at a temperature of 15° C. to 25° C. and maintaining a pH value of 3 to 6 to ripen the mixed slurry.

12. The method for preparing the modified ceramic coating according to claim 8 or 9, characterized in that: In the mixed slurry, the weight portion of the modified polyetheretherketone is 0.2-1.0 parts, the weight portion of the polysiloxane is 30-40 parts, the weight portion of the silica sol is 10-15 parts, and the weight portion of the solvent is 10-30 parts; or, The mixed slurry also includes pigments and fillers and solvents, wherein in the mixed slurry, the weight portion of the modified polyetheretherketone is 0.1 parts to 0.5 parts, the weight portion of the polysiloxane is 30 parts to 40 parts, the weight portion of the silica sol is 10 parts to 15 parts, the weight portion of the pigments and fillers is 20 parts to 30 parts, and the weight portion of the solvent is 10 parts to 30 parts.